Role of dialysate sodium and serum sodium gradient in intradialytic hypertension of regular hemodialysis patients - Mohamed M Fayed; Emad A Mohamed; Hindawy A Zidan; Ahmed A Assem; Moahmed A El-Sayed (Wolters Kluwer Medknow Publications, 2022)
Background and aim Sodium (Na+) balance largely depends on interdialytic dietary salt intake and intradialytic Na+ removal during hemodialysis (HD) for chronic renal failure cases. To preserve a normal Na+ equilibrium, interdialytic Na+ increase should be filtered during HD. Sodium gradient (Na+ G) is obtained by subtraction of the dialysate Na+ concentration and the patient's own pre-HD plasma sodium concentration. The aim was to evaluate the role of dialysate and serum Na+ G in patients with intradialytic hypertension (IDH). Patients and methods A cross-sectional observational study was done to evaluate the role of Na+ G in IDH in a cohort of HD patients followed in the dialysis center of Damanhur Fever Hospital. Among 119 prevalent patients on MHD in our center during period from March 2021 to July 2021, we found 26 patients with IDH, so we selected a control group of 26 patients with intradialytic normotension (age and sex matched). So, the study included 52 patients (age and sex matched) who were divided into two groups: group A included 26 patients who were intradialytic normotensive, and group B included 26 patients with IDH. Results A total of 52 patients were included in our final analysis. The sample included patients who are diagnosed with ESRD and under regular HD schedule, with a mean±SD age of 54.4±12.3 years. Comparison of different sodium concentrations revealed that there was no significant difference between pre-dialytic, and postdialytic Na serum levels, along with no difference in sodium gradients, with P values greater than 0.05. Conclusion IDH was not significantly associated with sodium gradient, age, sex, hemoglobin level, and predialytic and postdialytic serum sodium concentrations.